The Long Shadow of Malay kitab jawi Publishing in the Hejaz and Cairo - Bruckmayr, Philipp (Oriente moderno, 2025)
Between the 1880s and 1960s an industry for the production of Islamic books in the Malay language and its adaptation of the Arabic script, the so-called kitab jawi, developed in the Hejaz and Cairo. It was the result of collaboration by Malay authors and editors, Arab and Ottoman state presses and private publishers, and local booksellers, many of whom were of Indian descent. This study identifies the key actors in kitab jawi publishing in the Hejaz, Cairo and, to a lesser extent, Istanbul. Thereby it sheds light on the role played by Middle Eastern kitab jawi printing for community formation among Southeast Asian Muslims and on how its function contrasted with that of periodicals in this regard. Furthermore, it shows how the legacy of Middle Eastern kitab jawi editions, as an instructive testimony to transregional Islamic connections and cross- cultural cooperation, lives on until the present day.